Dispositivo atomizador con contenedores de material en aerosol sin presión - GUTSMANN, Volker; REID, Byron (2024)
La invención se refiere a la aplicación de sustancias activas líquidas con ayuda de un dispositivo pulverizador portátil. El objeto de la presente invención es un dispositivo portátil para aplicar sustancias activas y un método para aplicar sustancias activas con ayuda de un dispositivo pulverizador portátil. (Traducción automática con Google Translate, sin valor legal) The invention relates to the application of liquid active substances with the acid of a portable spray device. The subject matter of the present invention is a system comprising a portable spray device and a replaceable cartridge that contains an active substance concentrate. The invention also relates to method for applying a liquid active substance formulation. In addition, the invention discloses a replaceable cartridge that has a memory unit in which information is stored relating to an adjustable dilution ratio for the active substance concentrate contained in the cartridge. The invention also relates to a spray device comprising a control unit that can be read out a memory unit of cartridge attached to the spray device and, on the basis of the read out information, adjust a dilution ratio for the active substance concentrate contained in the cartridge.